Kilka uwag o Konwencji Jakobińskiej, Komunie Paryskiej w 1871 r. i władzy radzieckiej: [Some remarks on Jacobin Convention, paris Commune of 1871 and Soviet power] (Studia Prawnicze / The Legal Studies, 1981)
The Author supposes that the rule of the Jacobin Convention during the French Revolution (1793-1794) and that of Paris Commune (1871) embodied the concept of ruling which influenced Lenin’s political thoughts and the contents of the constitution of the Russian Federal Socialist Soviet Republic of 1918, which was a model for the constitutions of other soviet republics as well as for the constitution of the Soviet Union of 1924.This concept consits in: concentration of power in a chosen assembly (the rule of the assembly), control of the people(voters) over the representatives and over the apparatus of administration, vertical delegation of power and collegiality of executory organs. The rule of Jacobins from April 1793 to Thermidor were the example of the rule of a party.Circumstances which accompanied establishing of soviet power in Russia promoted making use of the principles of ruling which derive from the thoughts and experience of Jacobin Convention and Paris Commune. After the death of Lenin and especially in the thirtees in result of phenomenon generally known as "the cult of an individual” this power diverged from democratic principles.